It would depend on the context ... For example, if it were conversational inflammatory, you might say 'you vicious sadistic bastard' 'Heartless savage' works too ... Either of these work well to get the idea across and are definitely something that would...

## Answers by Susan L.

Sorry, it is not possible to answer the questions without the actual values in the problem ... how many kph (kilometers per hour) is each of the cars traveling?

So the approach here is that we NEED to isolate all values that contain L on ONE side of the equation 2LH + 2LW = 2WH You can factor 2L out of the left side to get: 2L(H + W) = 2WH Divide BOTH sides by 2(H+W) 2L(H+W) ...

Well, I would be happy to answer -- but your problem doesn't make any sense If you are wanting to use distributive property, there are typically parenthesis in the problem For example, if your problem looks like (m - 3)(m + 5) Then you distribute...

t^2 - 10t + 21 So you need to FACTOR this quadratic ... the easiest way is to realize that since the FINAL value (+21) is positive, it either has 2 negative or 2 positive factors. NOW look at the MIDDLE term, since it is NEGATIVE - this tells you that you want to make...

Well, point slope form of an equation follows this form: (y2 - y1) = m(x2 - x1) So using the m=1 (-5, -7) substituted into it yoy get: (y - -7) = 1 (x - -5) Since the 2 minuses become a plus, we finally have (y + 7) = 1(x +...

So from your choices, the y+4 = 1/2(x-1) would be the correct answer The point-slope formula say y2 - y1 = m (x2 - x1) So you fill in your values of m = 1/2, x1 = 1 and y1 = -4 This results in y - -4 = 1/2(x-1) y - -4 (two negatives make a positive) ==> y + 4 So...

My assumption without more information is that you need to put the equaton into a different form 6x= 7 - 4y --> this is the equation of a line There are multiple forms such an equation can take the most recognizable is the 'slope intercept' form which is y = ax + b...

So you have 12 + 3(2y-3) simplify typically means to 'combine like terms' in order to do that in this problem, you need to 'distribute' the 3(2y-3) 12 + 3(2y - 3) 12 + (3*2y) + (3*-3) --> distribute the 3 across the members inside the parenthesis 12 + 6y...